Cryptococcal antigen prevalence in HIV‐infected Tanzanians: a cross‐sectional study and evaluation of a point‐of‐care lateral flow assay. Issue 9 (13th August 2013) - Rugemalila, Joan; Maro, Venance P.; Kapanda, Gibson; Ndaro, Arnold J.; Jarvis, Joseph N.
Abstract Objectives Cryptococcal antigen (CRAG) screening at antiretroviral therapy (ART) initiation and pre‐emptive antifungal treatment for those testing positive could prevent many cases of cryptococcal meningitis (CM). To investigate whether CRAG screening would be feasible in Tanzania, we conducted a cross‐sectional study measuring CRAG prevalence in ART clinic patients and comparing the novel lateral flow assay (LFA) with the cryptococcal latex agglutination (LA) test. Methods Consecutive HIV‐infected outpatients with CD4 counts <200 cells/µL, who were ART naive or had been on ART for <6 months, were screened for CRAG using the LA and LFA kits. For further assay validation, HIV‐infected inpatients with suspected cryptococcal disease were also tested using the LA and LFA kits. Results Cryptococcal antigen was detected in seven of 218 ART clinic attendees (3%). Six patients (5%) with CD4 cell counts ≤100 cells/µL (n = 124) were CRAG‐positive. Agreement between the LA and LFA test in the 218 outpatients was 100%. Another 101 inpatients were tested for CRAG, of whom 56 (55%) were CRAG‐positive on both the LA and LFA tests. One patient was positive using the LFA test but negative on the LA test. The overall agreement between the two assays was 99.7%, kappa coefficient 0.99 (standard error 0.06, P < 0.001). Conclusions Five percentage of ART clinic patients with CD4 cell counts ≤100 cells/µL in northern Tanzania had asymptomatic cryptococcal antigenaemia, suggesting that CRAG screening would be worthwhile in the Tanzanian ART programme. The LFA is a reliable, cheap and practical alternative to LA for detection of CRAG.